Liberalisasi Importasi Produk Pertanian dalam UU Cipta Kerja dari Pemikiran Hukum Progresif - Hendriyanto, Kessa (PROGRESIF: Jurnal Hukum, 2020)
Regulations are chosen as a means to realizizing public policy by the Government. Law Number 11 of 2020 concerning Job Creation (Job Creation Law), as an omnibus law, was formed to create a conducive climate for investment by reforming regulations in the field of business licensing. In its journey, the Job Creation Law is inseparable from various polemics, starting from the reporting stages of the material regulated in it, including efforts to liberalize food import policy. Allegedly, the presence of the Job Creation Law is injustice and negates the little people. The progressive law put forward by Satjipto Rahardjo adheres to the understanding that law is said to be progressive when the law favors the weak, the law must be pro-justice and pro-people. Based on the study and analysis of progressive law on the Job Creation Law, it can be said that the content of the Job Creation Law in agriculture which is an effort to liberalize food imports is also not in line with progressive law because it does not pay attention to the interests of small farmers because it reduces farmers' right to life.